Dietas hiperlipídica, normolipídica e hipolipídica com baixa relação ômega 6/ ômega 3 e alta ômega 9/ ômega 6 na carcinogênese cólica em ratos - Burlamaqui, Idália Maria Brasil (2014)
Colorectal cancer has a high incidence and is known to be influenced by dietary factors. The fatty acids -3, -6 and -9 are believed to be involved in its genesis and prevention. The objective was to evaluate the effect of hyperlipidic, normolipidic and hypolipidic diets with low -6:-3 ratio and high -9:-6 ratio on azoxymethane (AOM) induced colorectal carcinogenesis in rats. Sixty 3-week-old male Wistar rats weighing 40-50g were assigned to 5 groups of 12 each: GI=Standard diet without AOM; GII=Standard diet and AOM; GIII=Hyperlipidic diet and AOM; GIV=Normolipidic diet and AOM; GV=Hypolipidic diet and AOM. Weight and ingestion were registered 4 times/week until the 36th week. Colons were analyzed for tumors, aberrant crypt foci, number of crypts per focus, incidence, differentiation, invasion and carcinoma multiplicity. The levels of total and fractionated cholesterol, triglycerides, glycemia, ALT, AST, glutathione, TBARS, interleukins were determined in plasma. Apoptosis, mitosis, NFkB, COX-2 and K-Ras were measured in tumor tissue. Body mass was greater in GI and GII than in GIII, GIV and GV. Ingestion was greater in GI and GII than in GIII, GIV and GV. The number of aberrant crypts and the total number of foci with <5 and >5 crypts decreased in GIV and GV compared to GII. In GV, the incidence of tumors was reduced. The index of carcinogenesis was higher in GII than in GV. Glutathione was higher and TBARS was lower in GV. GIII was higher than in GI with regard to IL-10. IFNγ was higher in GII than in GIII and GV. TNF-α was higher in GIV and GV than in GI. Apoptosis increased in GV, GIV and GIII in relation to GII and GI. The mitotic index was lower in GV than in GII, GIII and GIV. In conclusion, hyperlipidic, normolipidic and hypolipidic diets with low -6:-3 ratio and high -9:-6 ratio reduce ingestion, body mass and lipid peroxidation; increase the antioxidant capacity and offer protection against colorectal carcinogenesis.